Transplantace srdce--minulost, soucasnost a výhled do budoucna - Spinarová, L (Vnitrni lekarstvi, 2010)
We provide an overview of the history, current status and future perspectives of heart transplantations. We describe indication criteria and possible post-transplantation complications. Finally, we list the options that could, as an alternative, complement transplantations in the future. This is mainly the use of mechanical heart support devices.
Keywords: Forecasting; Heart Transplantation; Humans; lidé; transplantace srdce; předpověď